Empirical Analyis of Public ICT Development Project Objectives in Hungary - Aranyossy, Márta; Nemeslaki, András; Fekó, Adrienn (International journal of advanced computer science & applications, 2014)
E-government development in most European countries was ensured from Structural Funds in the period of 2007-2014. In our paper we show how Hungary has used these funds in order to achieve efficiency and effectiveness in its public services. The main objective of our research has been to explore the budgetary and timing characteristics of public ICT spending, and analyze the implicit and explicit objectives of eGovernment projects in Hungary. We applied exploratory text analyzes as a novel and objective way to analyze the focus of eGovernment development policy. Our main findings are: - After the text analysis of 85 Electronic Public Administration Operational Programme (EPAOP) and 65 State Reform Operational Programme (SROP) projects we found that keyword statistics are generally consistent with the main policy level objectives of the Operative Programmes, however there are some fields which are not emphasized, such as: the role of participation, social partners, local-government; and the improvement need of user skills through public information campaigns. - Governmental changes are clearly reflected in the goal hierarchy: contracting in EPAOP and SROP happened in two separate waves - the significant part of financing was committed during stabilized governments in the beginning and end phase of the planning period, with a relatively passive period during governmental change in 2010-2011.